KAJIAN ASPEK SEMANTIK ISTILAH KEAGAMAAN PADA TEKS THE CULTURAL ATLAS OF ISLAM(Studi Evaluatif Melalui Pendekatan Kritik Holistik) - Kardimin, Kardimin (Universitas Ahmad Dahlan, 2014)
Today the efforts of translation of books of science and technology in Indonesia is increasingly necessary. The need for translation business is done in both areas was caused by several things. First as a developing country, Indonesia wants to improve its progress in the field of science and technology. Second, most of the science and technology books written in foreign languages. Third, the ability of our scholars to write original work in both areas was very limited.This study uses a holistic approach to criticism. In criticism of holistic, objective factors that were examined in this study is the book Indonesian translation